COVID-19: Emergence, spread and its impact on the Indian economy and migrant workers - Ashok Gulati; Shyma Jose; B. B. Singh (University of Bonn, Center for Development Research (ZEF), 2021)
This study examines the impact of the Covid-19 pandemic and the related nationwide lockdown on the Indian economy, particularly on food systems. It also takes up an important issue of millions of migrant workers in India who seem to have suffered the most during this period. The loss of their livelihood, incomes, and food insecurity are captured through a survey of 2917 migrant workers in six different states of India. At the end, the study gives recommendations on how to broaden the support for migrant workers nationwide. [...] To revive the economy and provide support to vulnerable populations, the central government announced a series of packages. These included an additional quantity of subsidised food-grains under the Public Distribution System (PDS), cash transfers through Jan Dhan Yojana, free gas supply under the Ujjwala scheme, an ex-gratia to widow/senior citizen as well as income transfer to farmers under PM-Kisan. Overall, our survey showed 84.7 percent of the migrants had access to subsidised cereals under PDS, while the percentage receiving pulses was much lower at 12 percent during NovemberDecember 2020. Moreover, only 7.7 percent of migrants in their native place reported being engaged in Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) or any other public work. The demand-driven skill training under GKRY reached only 1.4 percent of migrants at their native place in our survey. Many workers reported a fall in the quality of food consumed during the lockdown and post-lockdown compared to the pre-lockdown level. With no access to relief measures and entitlements, a quick recovery of the migrant workers seems grim.
Keywords: H55; I15; I18; J61; 330; Covid-19; lockdown; food system; migrants; India